Penguatan tata kelola zakat dan wakaf untuk meningkatkan kepercayaan publik - Aini, Dewi Khoiriyatul; Wardana, Guntur Kusuma (Maliki Interdisciplinary Journal, 2026)
Zakat and waqf serve as vital tools within the Islamic economy, contributing to the enhancement of social and economic welfare for communities. The administration of zakat and waqf continues to encounter numerous challenges, particularly the lack of public trust in the managing institutions. This research aims to assess the strengthening of the governance of zakat and waqf to bolster public confidence. The research methodology employed is a qualitative approach, utilizing literature review through the examination of various journals, books, and pertinent scientific resources. The discussion’s findings indicate that the implementation of good governance principles such as transparency, accountability, professionalism, and responsibility plays a crucial role in establishing more effective and trustworthy management of zakat and waqf. Moreover, the application of Sharia accounting standards can enhance the quality of financial reporting, making fund management more transparent and comprehensible to the public. The utilization of digital technology also positively impacts the efficiency of services, information accessibility, and the ease with which the community can channel zakat and waqf. By reinforcing sound governance practices, public trust in zakat and waqf institutions can increase, leading to more optimal and sustainable management of community funds.